2006
DOI: 10.1308/003588406x94977
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Facial Wounds in UK Accident and Emergency Departments

Abstract: A 16-year-old male with a simple but dirty wound over the right cheek. B 23-year-old female with a complex wound to the lower lip. C 65-year-old male with an extensive laceration to the forehead. RESULTS There was a 76% response rate. Suturing was the preferred method of closure, with the majority of clinicians preferring 6/0 or 5/0 non-resorbable sutures. Use of a regional nerve block would be considered by a quarter of clinicians, and adrenaline vasoconstrictor by a third. Referral rates ranged from 5-77% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In the present study’s results, 71.7% of simple facial lacerations were repaired by an ED resident ( Table 1 ). In the UK, 50% to 90% of simple facial lacerations are repaired by accident and ED doctors; the rest of them are referred to other specialists [ 2 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study’s results, 71.7% of simple facial lacerations were repaired by an ED resident ( Table 1 ). In the UK, 50% to 90% of simple facial lacerations are repaired by accident and ED doctors; the rest of them are referred to other specialists [ 2 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A propensity score was developed using logistic regression to estimate the probability of being assigned to the participant group compared with the nonparticipant group. Relevant covariates were identified from known risk factors for wound complications and precision of discrimination and propensity score calibration were analyzed using the c‐statistic and Hosmer‐Lemeshow goodness‐of‐fit test. Matching was not performed using provider status because all the wounds were repaired by a pair of physicians (an intern with a board‐certified emergency physician or a resident with a board‐certified emergency physician) and board‐certified emergency physicians were always involved in wound closure, as well as because unmeasurable differences in suturing skills among each provider status would potentially exist.…”
Section: Methodsmentioning
confidence: 99%
“…Although patients may prefer facial trauma specialists, such as plastic surgeons, oral and maxillofacial surgeons, or otolaryngology/head and neck surgeons, to close their facial wounds to obtain the best possible outcome, the distribution of facial trauma coverage by specialists at the ED is regionally dependent . Studies have shown that a considerable number of facial wounds were repaired by nonspecialists, including emergency physicians, general surgeons, and registered nurses . A 2015 retrospective observational study of patients with facial lacerations found that more than 70% of patients underwent repair by a nonspecialist .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The analysis shows there are clear financial implications to this outdated model and coding arrangements, 4 especially as the service model is commonplace within OMFS units across the UK. 5 We have proposed and costed an alternative service model, similar to other acute surgical specialities, where patients return to the treating department when safe to do so as part of a scheduled trauma list (often run daily by a trainee with additional senior support available). Such trauma lists can also maximise use of re-usable instrument trays which are sterilised through theatre services, minimising single use item waste to reduce cost and become more sustainable.…”
Section: Sirmentioning
confidence: 99%